2021
DOI: 10.3390/buildings11120618
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Formwork System Selection Criteria for Building Construction Projects: A Comparative Study

Abstract: The formwork system (FWS) in reinforced concrete (RC) construction is a critical component. The appropriate FWS is selected based on a number of conflicting and compromising criteria, and the selection of the FWS is carried out by construction professionals with different technical and/or administrative backgrounds. The perspectives and perceptions of construction professionals and companies involved in the FWS selection process may vary depending on their motives. In addition, some building structural paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 89 publications
0
19
0
Order By: Relevance
“…However, no study has identified the quantitative effects among FWS selection criteria groupings. Terzioglu et al [32] suggested performing factor analysis and SEM technique on FWS selection criteria, which may reveal important quantitative effects among FWS selection criteria groupings. These quantitative effects, if any, can be used to improve the FWS selection process in building construction projects and, consequently, the project performance factors [32].…”
Section: Studies Related To the Application Of Mcdm Methods For The F...mentioning
confidence: 99%
See 4 more Smart Citations
“…However, no study has identified the quantitative effects among FWS selection criteria groupings. Terzioglu et al [32] suggested performing factor analysis and SEM technique on FWS selection criteria, which may reveal important quantitative effects among FWS selection criteria groupings. These quantitative effects, if any, can be used to improve the FWS selection process in building construction projects and, consequently, the project performance factors [32].…”
Section: Studies Related To the Application Of Mcdm Methods For The F...mentioning
confidence: 99%
“…Terzioglu et al [32] suggested performing factor analysis and SEM technique on FWS selection criteria, which may reveal important quantitative effects among FWS selection criteria groupings. These quantitative effects, if any, can be used to improve the FWS selection process in building construction projects and, consequently, the project performance factors [32]. To the authors' knowledge, no studies involving formwork or FWS selection have employed the SEM approach.…”
Section: Studies Related To the Application Of Mcdm Methods For The F...mentioning
confidence: 99%
See 3 more Smart Citations